Cloning and Expression of Canine Glycoprotein Ibα - Kenny, Dermot; Morateck, Patricia A.; Fahs, Scot A.; Warltier, David C.; Montgomery, Robert R. (Thrombosis and Haemostasis, 1999)
The interaction of the glycoprotein (GP) Ib-IX-V complex with von Willebrand factor (vWF) is critical in initiation of haemostasis and thrombosis through platelet adhesion to damaged endothelium. The binding site for vWF resides within the GPIbα subunit of the complex. To further define the physiological function of platelet GPIbα we cloned and expressed the canine GPIbα cDNA. A canine platelet cDNA library was constructed and screened with a randomly primed 32P-labeled 1041-base-pair restriction fragment of the human GPIbα cDNA. Analysis of 23 clones demonstrated that the canine GPIbα cDNA is 2530 nucleotides in length and includes a short 5’ untranslated segment of 42 nucleotides followed by a signal peptide of 16 amino acids, a mature peptide of 645 amino acids and a 3’ noncoding region of 455 nucleotides. A single intron of 142 nucleotides, 6 nucleotides upstream from the ATG translation initiation codon was identified in the canine gene in a similar location to that present in the human gene.Chinese hamster ovary cells that stably express human GPIbα and GPIX were transfected with the canine GPIbα cDNA. Canine GPIbα was expressed on the surface of these cells and bound vWF in the presence of botrocetin. The binding of vWF was inhibited by an anti-vWF human monoclonal antibody known to inhibit vWF binding to GPIbα. The results of this investigation will allow the development of reagents to study the physiological function of GPIbα in an animal model.